A National, Electronic Health Record–Based Study of Perinatal Hemorrhagic and Ischemic Stroke. (March 2023) - Fraser, Stuart; Levy, Samantha M.; Talebi, Yashar; Savitz, Sean I.; Zha, Alicia; Zhu, Gen; Wu, Hulin
Background: Perinatal stroke occurs in approximately 1 in 1100 live births. Large electronic health record (EHR) data can provide information on exposures associated with perinatal stroke in a larger number of patients than is achievable through traditional clinical studies. The objective of this study is to assess prevalence and odds ratios of known and theorized comorbidities with perinatal ischemic and hemorrhagic stroke. Methods: The data for patients aged 0-28 days with a diagnosis of either ischemic or hemorrhagic stroke were extracted from the Cerner Health Facts Electronic Medical Record (EMR) database. Incidence of birth demographics and perinatal complications were recorded. Odds ratios were calculated against a control group. Results: A total of 535 (63%) neonates were identified with ischemic stroke and 312 (37%) with hemorrhagic stroke. The most common exposures for ischemic stroke were sepsis (n = 82, 15.33%), hypoxic injury (n = 61, 11.4%), and prematurity (n = 49, 9.16%). The most common comorbidities for hemorrhagic stroke were prematurity (n = 81, 26%) and sepsis (n = 63, 20%). No perinatal ischemic stroke patients had diagnosis codes for cytomegalovirus disease. Procedure and diagnosis codes related to critical illness, including intubation and resuscitation, were prominent in both hemorrhagic (n = 46, 15%) and ischemic stroke (n = 45, 8%). Conclusion: This electronic health record–based study of perinatal stroke, the largest of its kind, demonstrated a wide variety of comorbid conditions with ischemic and hemorrhagic stroke. Sepsis, prematurity, and hypoxic injury are associated with perinatal hemorrhagic and ischemic stroke, though prevalence varies between types. Much of our data were similar to prior studies, which lends validity to the electronic health record database in studying perinatal stroke.